The Effect of Absorptive Capacity on Supply Chain Innovation Performance through Supply Chain Resilience in Manufacturing Companies: Empirical Study From Bogor Region, Indonesia - Tobing, Angelyn E Nauli; Santosa, Wahyuningsih (Manunggal Halim Jaya, 2025)
This study examines the impact of digital capabilities on supply chain innovation performance through digital innovation in manufacturing companies in Bogor. In the advancing digital era, an organization's ability to leverage digital technology is crucial for achieving a competitive advantage. The research adopts a quantitative approach using a questionnaire survey. Convenience sampling and snowball sampling methods were employed to gather a sample size of 133 respondents. The data were analyzed using Structural Equation Modeling (SEM) to test the relationships between absorptive capacity, supply chain resilience, and supply chain innovation performance. The results indicate that absorptive capacity positively influences supply chain innovation performance (P-value 0.0245 < 0.05) with a positive estimated value of 0.134. However, absorptive capacity does not significantly affect supply chain resilience (P-value 0.310 > 0.05). Additionally, supply chain resilience does not positively impact supply chain innovation performance, as shown by a P-value of 0.032 < 0.05 but with a negative estimated value of -0.134, indicating a negative effect. The hypothesis that absorptive capacity influences supply chain innovation performance through supply chain resilience is not supported. In conclusion, while absorptive capacity can directly enhance innovation performance, other factors such as risk management and supply source diversification need to be addressed to improve supply chain resilience. This study suggests that strengthening employee training and development will enhance absorptive capacity and recommends exploring additional factors that may facilitate the integration of absorptive capacity and innovation in the supply chain. Further qualitative research is needed to explore other factors that influence these relationships.